2013
DOI: 10.1007/s00439-013-1298-z
|View full text |Cite|
|
Sign up to set email alerts
|

Sex- and age-dependent DNA methylation at the 17q12-q21 locus associated with childhood asthma

Abstract: Chromosomal region 17q12-q21 is one of the best-replicated genome-wide association study (GWAS) hits and associated with childhood-onset asthma. However, the mechanism by which the genetic association is restricted to childhood-onset disease is unclear. During childhood, more boys than girls develop asthma. Therefore, we tested the hypothesis that the 17q12-q21 genetic association was sex-specific. Indeed, a TDT test showed that in the Saguenay-Lac-Saint-Jean familial collection, the 17q12-q21 association was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 44 publications
1
54
1
1
Order By: Relevance
“…Correlations have been found between all nine CGs using Pearson's correlation tests (correlation coefficients between 0.5 and 1.0), allowing us to analyse average methylation levels for all nine CGs. Since earlier we have found that ZPBP2 methylation levels depended on the sex of individuals in HapA homozygotes,17 the effect of sex on methylation had to be confirmed for other genotypes. Methylation levels were significantly higher in females compared with males in models considering haplotypes and those results were significant independent of white blood cell counts in agreement with our earlier findings (p=7.6E-13 (previously reported in ref.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Correlations have been found between all nine CGs using Pearson's correlation tests (correlation coefficients between 0.5 and 1.0), allowing us to analyse average methylation levels for all nine CGs. Since earlier we have found that ZPBP2 methylation levels depended on the sex of individuals in HapA homozygotes,17 the effect of sex on methylation had to be confirmed for other genotypes. Methylation levels were significantly higher in females compared with males in models considering haplotypes and those results were significant independent of white blood cell counts in agreement with our earlier findings (p=7.6E-13 (previously reported in ref.…”
Section: Resultsmentioning
confidence: 87%
“…To test the relationship between genotype, DNA methylation and asthma, we analysed promoter methylation levels of those genes where the effect of genotype on expression was previously demonstrated, i.e, ZPBP2 , GSDMB , ORMDL3 and GSDMA, 19 25 27 28 in DNA samples from peripheral blood of subjects from the SLSJ asthma familial collection (table 1). 17 The ORMDL3 promoter was hypomethylated while the GSDMB promoter was hypermethylated in all samples with no evidence for effect of genotype or disease on methylation (see online supplementary table S4). Methylation of the ZPBP2 and GSDMA promoters varied considerably among individuals.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Secondly, the suppression of ZPBP2 activity by 108 epigenetic methylation is greater in females than it is in males, providing a biochemical explanation 109 for why only one sex is affected by the variant (Naumova et al 2013), pending further investigation of 110 tissue-specific methylation profiles. The reason why ZPBP2 is expression is not suppressed in males is 111 possibly because it has an important role in production of viable sperm, but with no known phenotype 112 in females, as determined from gene knock-out studies in mice (Y.-N. Lin et al 2007).…”
mentioning
confidence: 99%